Comparison of the Educational Environment at a Medical College under Two Different Curricula - Ayesha Younas; Robina Mushtaq; Rafia Minhas; Moatter Jahan (Journal of the Dow University of Health Sciences, 2020)
Objective: To compare the perception of students regarding the educational environment at a medical college which underwent a curricular change using the Dundee Ready Education Environment Measure (DREEM) at two different points in time.